KINERJA KOMITE SEKOLAH DALAM MENINGKATKAN KUALITAS PENDIDIKAN DI SMP AL-KHAIRAAT KALUMPANG KOTA TERNATE - Ismail, Anwar (Universitas Khairun, 2015)
The purpose are (1) to know the school committee to improve the quality of education at SMP Al-Khairaat Kalumpang Ternate; ( 2 ) to know the work achievement of school committee to improve the education qualityÂ at SMP Al-Khairaat Kalumpang Ternate.The approaches used in this research is a qualitative approach.Research result indicates that ( 1 ) a school committee at SMP Al-Khairaat Kalumpang Ternate has formed by 2012 in accordance with the decree no. 325 / B-III / SMP.BP. Alkh / 11 / 2010 and has the school committee structure, namely; chief; secretaries, and the treasury; ( 2 ) the school committee meeting periodically, that is four times in a year. Involved in the talks is the principal, the teacher, student parents, Al-Khairaat foundation and the school committee. Things had been spoken in the meeting are; the school fee, standards graduation, the school programs plan ; ( 3 ) the school committee does not make a written report yet orally. This is a form of violations Kepmendiknas number 044 / u / 2002 about the school committee.( 4 ) the school committee ' s active, this could influence the development of education at SMP Al-Khairaat Kalumpang Tenate.It is a part breach Kepmendiknas number 044 / u / 2002 about the school committee.Â The keywords:Â performance, the quality, the school committee